Results of the 2014 SRS Survey on PJK/PJF: A Report on Variation of Select SRS Member Practice Patterns, Treatment Indications, and Opinions on Classification Development. Issue 11 (1st June 2015) - Scheer, Justin K.; Fakurnejad, Shayan; Lau, Darryl; Daubs, Michael D.; Coe, Jeffrey D.; Paonessa, Kenneth J.; LaGrone, Michael O.; Amaral, Rodrigo A.; Trobisch, Per D.; Lee, Jung-Hee; Fabris-Monterumici, Daniel; Anand, Neel; et al.
Abstract : Study Design: An electronic survey administered to Scoliosis Research Society membership. Objective: To characterize surgeon views regarding proximal junctional kyphosis (PJK) and proximal junctional failure (PJF) management providing the framework in which a PJK/PJF classification system and treatment guidelines could be established. Summary of Background Data: PJK/PJF are common complications of adult spinal deformity surgery. To date, there is no consensus on PJK/PJF definitions, classification, and indications for revision surgery. There is a paucity of data on deformity surgeon practice pattern variations and consensus opinion on treatment and prevention. Methods: An electronic 19-question survey regarding PJK/PJF was administered to members of the Scoliosis Research Society who treat adult spinal deformity. Determinants included the surgeons' type of practice, number of years in practice, agreement with given PJK/PJF definitions, importance of key factors influencing prevention and revision, prevention methods currently used, and the importance of developing a classification system. Results: A total of 226 surgeons responded (38.8% response rate). Both 44.4% of surgeons selected "extremely important" and 40.8% selected "very important" that PJK in adult spinal deformity surgery is a very important issue and that a Scoliosis Research Society PJK/PJF classification system and guidelines for detection and prevention of PJK/PJF is a "must have" (18.1%) and "very likely helpful" (31.9%). Both 86.2% and 90.7% of surgeons agreed with the provided definitions of PJK and PJF, respectively. Top 5 revision indications included neurological deficit, severe focal pain, translation or subluxation fracture, a change in kyphosis angle of greater than 30°, chance fracture, spondylolisthesis greater than 6 mm, and instrumentation prominence. The majority of respondents use a PJK/PJF prevention strategy 60% of the time or more, the most common were terminal rod contour, preoperative bone mineral density testing, and frequent radiographical studies during first 3 months postoperative, preoperative bone mineral density medication for low bone mineral density. Conclusion: The results of this study provide insight from the practicing surgeons' perspective of the management of PJK and PJF that may aid in the validation of current definitions and consensus-based treatment decisions and prevention guidelines. Level of Evidence: 5 Abstract : A total of 226 surgeons completed an international electronic survey regarding proximal junctional kyphosis/proximal junctional failure (PJK/PJF). Definitions, prevention strategies, and operative indications were determined. The results of this study provide insight from the practicing deformity surgeons' perspective on the management of PJK and PJF that may aid in the formation of a new classification system.